Geoff Emberling & Katharyn Hanson (ed.), Catastrophe! The Looting and Destruction of Iraq’s Past. The Oriental Institute Museum of the University of Chicago, Number 28. Chicago, The Oriental Institute of the University of Chicago, 2008, con mapas e imágenes a color. ISBN 1–885923–56–2. U$D 29.95. - Béccar, Julieta (2009)
Fil: Béccar, Julieta. Pontificia Universidad Católica Argentina; Argentina